2007
DOI: 10.4095/223784
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution seismic survey from the McArthur River region: contributions to mapping of the complex P2 uranium ore zone, Athabasca Basin, Saskatchewan

Abstract: The primary objective of the high-resolution survey was to offer a detailed subsurface image of the complex P2 fault zone, hosting the world's largest high-grade uranium deposits. Raw seismic data have low signal-to-noise ratio; nevertheless the implemented processing procedure considerably improved its quality. Interpretation of the two lines integrates all available background information such as regional geology; structural, stratigraphic, and diagenetic features associated with the borehole information inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Annesley and Madore (1994) observed that the Wollaston-Mudjatik boundary, in the Wollaston Lake area, marks an abrupt change of lithology and structural style. However, to the southwest, Annesley et al (2005, and references therein), Gyorfi et al (2007), Hajnal et al (2010), among others, showed that this domain boundary is a highly heterogeneous transition zone both across and along strike.…”
Section: Significance Of the Wollaston-mudjatik Transition Zonementioning
confidence: 94%
See 1 more Smart Citation
“…Annesley and Madore (1994) observed that the Wollaston-Mudjatik boundary, in the Wollaston Lake area, marks an abrupt change of lithology and structural style. However, to the southwest, Annesley et al (2005, and references therein), Gyorfi et al (2007), Hajnal et al (2010), among others, showed that this domain boundary is a highly heterogeneous transition zone both across and along strike.…”
Section: Significance Of the Wollaston-mudjatik Transition Zonementioning
confidence: 94%
“…Annesley and Madore (1994) initially suggested that the WMTZ marks an abrupt change of structural style and speculated that it is a major crustal-scale thrust and (or) strike-slip zone. In contrast, Annesley et al (2005), Gyorfi et al (2007), and Hajnal et al (2007) suggested that the junction between the Wollaston and Mudjatik domains was wider, variable in width, and highly heterogeneous in terms of lithology, deformation style, and P-T conditions. But in all cases, the WMTZ is regarded as a fundamental tectonic boundary that reworked the Hearne margin during the THO .…”
Section: Geodynamic Significance Of the Wollaston-mudjatik Transitionmentioning
confidence: 98%
“…Line of section is shown as NW-SE in Figure 4A. B) Diagrammatic structural cross-section south of Key Lake, adapted from Tran (2001) and Györfi et al (2007), illustrates structural geometry of the Wollaston-Mudjatik transition zone that underlies the most economically productive area of the eastern Athabasca Basin. Line of section is shown as W-E in Figure 4A.…”
Section: Districtmentioning
confidence: 99%
“…In both the Athabasca and the McArthur basins, the importance of structural control has been recognized (Hoeve and Quirt, 1984;Baudemont and Pacquet, 1996;Baudemont and Federowich, 1996;Tourigny et al, 2007;Jefferson et al, 2007;Kyser and Cuney, 2015). Uranium is linked to ductile to ductile-brittle shear zones in the Eagle Point , Nabarlek (Wilde and Wall, 1987), and Jabiluka (Polito et al, 2005a,b) deposits, to faults in the McArthur and Dominique-Peter deposits (Györfi et al, 2007;and Baudemont and Fedorowich, 1996;respectively), to breccias in the case of the Shea Creek deposit (De Veslud et al, 2009), and to a complex combination of folding and brecciation in the Jabiluka deposit (Polito et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 99%